2007
DOI: 10.1017/s0007114507280572
|View full text |Cite
|
Sign up to set email alerts
|

Breast milk sodium concentration, sodium intake and weight loss in breast-feeding newborn infants

Abstract: Elevated breast milk (BM) Na concentration is regarded as responsible for elevated Na intake. To verify the clinical significance of milk Na concentration, we studied the relationship between BM Na þ concentration and infants' daily Na þ intake, infants' daily BM intake (DBMI) and percentage weight loss (%WL) in healthy newborn infants. All mothers who gave birth to a single healthy infant, between February and March 2004 at the Obstetric Clinic of University of Messina (Italy), were invited to participate if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…The exact consequence of SCM on infant development remains to be established. A relationship between severe mammary inflammation during SCM and poor weight gain or lower breast milk intake has been reported [43] 14 one breast in human, making possible for the unaffected breast to increase the milk output to maintain milk intake. Authors have suggested that the raise of sodium and inflammation in breast milk may be associated with reluctance to accept milk from the affected breast during SCM [17].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The exact consequence of SCM on infant development remains to be established. A relationship between severe mammary inflammation during SCM and poor weight gain or lower breast milk intake has been reported [43] 14 one breast in human, making possible for the unaffected breast to increase the milk output to maintain milk intake. Authors have suggested that the raise of sodium and inflammation in breast milk may be associated with reluctance to accept milk from the affected breast during SCM [17].…”
Section: Discussionmentioning
confidence: 96%
“…Antileukoproteinase 1 is secreted during experimental mastitis in animals [42]. α-defensins are microbicidal peptides produced notably by weight gain or lower breast milk intake has been reported [43] [17] [44]. SCM occurs frequently in one breast in human, making possible for the unaffected breast to increase the milk output to maintain milk intake.…”
Section: Discussionmentioning
confidence: 99%
“…7,18,24 No single measure could confirm that LS-II was initiated, 22 although cutoffs in the range of 3-18 mmol/L have been proposed after Day 3.…”
Section: Discussionmentioning
confidence: 99%
“…Manganaro et al 29 CMT ϭ 0 (n ϭ 37) or Ն1 (n ϭ 23). The 25 th and 75 th percentiles are demarcated by the box, the median is represented by the dark horizontal line, and the whiskers represent 1.5 multiplied by the interquartile range.…”
Section: Discussionmentioning
confidence: 99%